2011
DOI: 10.1590/s0100-69912011000600010
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidantes enterais em lesões de isquemia e reperfusão em ratos

Abstract: Enteral antioxidants in ischemia/reperfusion injuries in rats Enteral antioxidants in ischemia/reperfusion injuries in rats Enteral antioxidants in ischemia/reperfusion injuries in rats Enteral antioxidants in ischemia/reperfusion injuries in rats Enteral antioxidants in ischemia/reperfusion injuries in rats Antioxidantes enterais em lesões de isquemia e reperfusão em ratos Antioxidantes enterais em lesões de isquemia e reperfusão em ratos Antioxidantes enterais em lesões de isquemia e reperfusão em ratos Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The beneficial effects of different antioxidants, especially vitamins C and E, are well documented in various disease models in both rodents and humans [ 138 , 139 , 140 , 141 , 142 ]. However, some demerits have also been reported for some of these antioxidants or vitamins [ 143 ].…”
Section: Could Honey Be a Better Antioxidant Than Some Of The Commmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effects of different antioxidants, especially vitamins C and E, are well documented in various disease models in both rodents and humans [ 138 , 139 , 140 , 141 , 142 ]. However, some demerits have also been reported for some of these antioxidants or vitamins [ 143 ].…”
Section: Could Honey Be a Better Antioxidant Than Some Of The Commmentioning
confidence: 99%
“…Many of these constituents may produce synergistic antioxidant effects. Besides, unlike vitamin C or E which requires the other for regeneration into the active form [ 138 , 139 ], this may be unnecessary with the use of honey. If any of the antioxidant constituents in honey exhibits pro-oxidant properties, there would be sufficient antioxidants for its regeneration.…”
Section: Could Honey Be a Better Antioxidant Than Some Of The Commmentioning
confidence: 99%
“…In mice with myocardial ischemia and reperfusion, pretreatment of α-tocopherol, i.e., a fat-soluble vitamin with potent antioxidant activity, significantly decreased cardiac ROS production, neutrophil infiltration, and MPO activity [32]. Pretreatment with vitamins C and E markedly reduced lipid peroxidation products, increased antioxidant enzyme activity, and mitigated jejunal damage in animals with ischemia and reperfusion injury [9,33,34]. In this study, IIR rats administered oral posttreatment supplementation of vitamin C plus E showed significantly reduced plasma IL-6 and NOx (Table 4), jejunal TBARS levels (Table 3), and MPO activity (Fig 4C).…”
Section: Plos Onementioning
confidence: 99%
“…Evidence indicates that oxidative stress plays a key role in the pathogenesis of IIR injury [3]. For example, pretreatment with antioxidant vitamins, such as vitamins C and E, showed protective effects against IIR-induced intestinal morphological lesions and neutrophil infiltration, increased the end products of lipid peroxidation, and decreased glutathione and antioxidant enzyme activity, including superoxide dismutase, glutathione peroxidase, and catalase [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%